Evaluation of environmental condition: water and sediment examination of oxbow lakes - Tamás, Margit; Farsang, Andrea (Acta Geographica Debrecina Landscape & Environment series, 2011)
As a result of the river regulation a number of oxbow lakes have arisen in the floodplain of the Lower-Tisza. The floodplain lakes represent natural values and major recreation areas of the lowland region. Due to the human activity the oxbow lakes’ condition declined. It can be shown by the water quality, the channel discharge by deposit, the high eutrophication of the lakes and the heavy metal elevation of the sediment. Discovering these processes, analysing the condition and recultivation of the oxbow lakes came into prominence only in the past few years. Our research aims to conclude the current environmental pollution of the oxbow lakes from statistical analyses of the heavy metal content of the sediment and from the water quality data. The oxbow lakes have been classified by chemistry instead of chemical. Results of the research show differences between the floodplain oxbows and the lakes outside the dam in terms of the quality of the sediment and the nutrient content of the water.